1974
DOI: 10.1103/physrevc.10.975
|View full text |Cite
|
Sign up to set email alerts
|

Isospin-forbidden alpha decay of the 15.11-MeV state inC12

Abstract: The branching ratio I /I~, has been measured for the 15.11-MeV 1+ T = 1 state in "C. The result is I /I, "l = (4.1 + 0.9)%, in agreement with one previous measurement and in disagreement with another. The result was obtained by direct observation of the decay a particles from the reaction "C('He, a)"Ca 3a. The data are consistent with a sequential decay via the first excited state of 'Be.The 3a breakup of the 1+ T = 0 state at F. "=12. 71 MeV was also studied. The data in both cases were fitted with a model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 15 publications
2
62
0
Order By: Relevance
“…For the 1 + state in 12 C the effect of this interference is to deepen the minima between the three peaks such that the agreement with the data is significantly improved [5,6].…”
Section: B R-matrix Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…For the 1 + state in 12 C the effect of this interference is to deepen the minima between the three peaks such that the agreement with the data is significantly improved [5,6].…”
Section: B R-matrix Formulationmentioning
confidence: 99%
“…This was pointed out for the decay spectrum of the 12.71-MeV state in Ref. [5] where a modified R-matrix expression was given (Eq. (3) in Ref.…”
Section: B R-matrix Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…One obvious shortcoming is the lack of symmetrization of the final states that consist of three identical bosons. This affects the R-matrix expression for breakup via excited states in 8 Be, as we do not know the order of emission of the 3α particles [28]. It has been shown that symmetrization affects the single-α spectrum for the breakup of the 12 C 1 + state at 12.7 MeV [11], but it is assumed to be less significant in the 3α sum spectrum.…”
Section: R-matrix Formalismmentioning
confidence: 99%